2003
DOI: 10.1055/s-2003-812557
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corneal Thickness on Comparative Intraocular Pressure Measurements with Goldmann and Non-Contact Tonometers in Keratoconus

Abstract: The thin cornea has more influence on the measurement with NCT than GAT. The relative precision of NCT compared with GAT seems to be influenced by the corneal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 18 publications
0
1
2
Order By: Relevance
“…Also, NCT provides an accurate and objective method of measuring IOP with many advantages over traditional Goldmann tonometry. 17 20 However, NCT values were significantly higher than GAT values in other studies 5 , 7 , 8 , 21 nGAT and fGAT values were correlated in our study, and these values were significantly lower than NCT values.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Also, NCT provides an accurate and objective method of measuring IOP with many advantages over traditional Goldmann tonometry. 17 20 However, NCT values were significantly higher than GAT values in other studies 5 , 7 , 8 , 21 nGAT and fGAT values were correlated in our study, and these values were significantly lower than NCT values.…”
Section: Discussioncontrasting
confidence: 70%
“…In some studies, as in ours, no correlations were observed between corneal curvature, NCT, and GAT. 21 , 24 In the present study, there was also no correlation between nGAT and corneal curvature. No correlation was found between NCT and corneal curvature, whereas a negative correlation was found between GAT and corneal curvature.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation